2021
DOI: 10.3389/fphar.2021.694762
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol-Rich Extract of Olive Mill Wastewater Enhances Cancer Chemotherapy Effects, While Mitigating Cardiac Toxicity

Abstract: Cardiovascular toxicity remains one of the most adverse side effects in cancer patients receiving chemotherapy. Extra-virgin olive oil (EVOO) is rich in cancer preventive polyphenols endowed with anti-inflammatory, anti-oxidant activities which could exert protective effects on heart cells. One very interesting derivative of EVOO preparation is represented by purified extracts from olive mill waste waters, (OMWW) rich in polyphenols. Here, we have investigated the anti-cancer activity, of a OMWW preparation na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
(139 reference statements)
0
15
0
Order By: Relevance
“…Based on our previous published article on the cardioprotective properties of the A009 extracts against chemotherapy-induced damages in models of prostate cancers ( 11 ), we also tested whether a similar scenario could be observed with chemotherapeutic agents used in BC treatment, such as 5-FU and Doxo. We observed that the rat cardiomyocyte cell line H9C2 exhibited less reduced cell proliferation, when co-treated with the A009 + 5-FU ( Figure 5 ) or A009 + Doxo ( Figure 6 ), both at 48 and 72 h, as compared to 5-FU or Doxo alone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous published article on the cardioprotective properties of the A009 extracts against chemotherapy-induced damages in models of prostate cancers ( 11 ), we also tested whether a similar scenario could be observed with chemotherapeutic agents used in BC treatment, such as 5-FU and Doxo. We observed that the rat cardiomyocyte cell line H9C2 exhibited less reduced cell proliferation, when co-treated with the A009 + 5-FU ( Figure 5 ) or A009 + Doxo ( Figure 6 ), both at 48 and 72 h, as compared to 5-FU or Doxo alone.…”
Section: Resultsmentioning
confidence: 99%
“…A peculiar capability of polyphenols resides in their ability to target transformed malignant cells ( 40 ) also cooperating with chemotherapeutic agents ( 11 , 40 , 41 ), while sparing healthy cells or recovering healthy cells undergoing stress conditions and cellular damages ( 42 44 ). Based on this evidence and on our previous published article on the cardioprotective properties of the A009 extract against chemotherapy-induced damages, in models of prostate cancers, we tested whether a cardio-oncological prevention scenario could be observed, using chemotherapeutic agents used for BC treatment, such as doxorubicin and fluoropyrimidines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exceptional action of OMWW on LNCaP cells, observed only after 96 h incubation, was traced to a drastic increase in apoptosis, neither observed in DU145 nor PC3 prostate cancer, nor in lung or colon cancer cells [23]. Albini et al recently showed that OMWW enhances the effect of cisplatin chemotherapy on prostate cancer xenografts [24]. In the present investigation, we found no distinct increase of apoptotic events after OMWW exposure over a time period of 72 h. Therefore, exposure to OMWW, which inhibits bladder cancer cell growth along with reducing cell clone number and size, cannot be attributed to apoptosis.…”
Section: Discussionmentioning
confidence: 99%